Business Development of Cumi-cumi Product Made from Sweet Potatoes in Karangbangun Village, Karanganyar Regency - Rauf, Rusdin; Haryoto, Haryoto (Journal of Community Services and Engagement, 2020)
The program of community service began with the socialization of applications on the village government and partners. Furthermore, it introduced machinery/technology to create technology on partners. The purpose of the community service activity was to provide the skills in the production of cumi-cumi products from sweet potato to members of Aisyiyah, PKK, and Karang Taruna in Karangbangun Village - Karanganyar District. The community service program began with a socialization program by the village government and partners. Furthermore, machines and technology were introduced to partners. The training of cumi-cumi product making and packaging was given to the partners, as well as production assistance, to ensure that partners were skilled at processing the products independently. The results showed that the partners were skilled at producing cumi-cumi products and using the machines. Two new UMKMs were formed in the community service program. Partners have been packing the products with labeled, marketed the products locally, as well as getting income from these sales.